MODEL MATEMATIKA SENSOR MIKROKANTILEVER BERBASIS SISTEM PEGAS - Ratno Nuryadi (Jurnal Poli-Teknologi, 2011)
Microcantilever has attracted interest for researchers as sensor in the field of chemistry, physics, biology and environment. Varieties of both theoretical and experimental studies have been conducted to explore the potential and to increase the sensor performance. In the theoretical studies, various models and simulations have been done to explain the microcantilever sensing phenomenon. This paper presents a mathematical model based on a spring system to explain the process of molecules sensing by using microcantilever. As a result, the resonant frequency shift due to detection of molecules on the surface mikrokantilever can be seen and this indicates that this model can be used to explain the sensing process in the microcantilever-based sensors. Keywords : Microcantilever, sensor, spring system, simulation. ABSTRAK Mikrokantilever telah menjadi perhatian menarik bagi para peneliti untuk diaplikasikan sebagai sensor pada bidang kimia, fisika, biologi dan lingkungan. Berbagai studi baik teori maupun eksperimen pun telah dilakukan untuk menggali potensi dan meningkatkan perfomanya. Termasuk di dalamnya, model dan simulasi telah diusulkan untuk menerangkan fenomena sensing. Pada makalah ini akan dipaparkan model matematika berbasis sistem pegas untuk menerangkan proses sensing molekul dengan menggunakan mikrokantilever. Hasilnya, pergeseran frekuensi resonansi dari vibrasi mikrokantilever karena terdeteksinya molekul pada permukaan mikrokantilever dapat terlihat dan hal ini mengindikasikan bahwa model ini dapat dipakai untuk menerangkan proses sensing pada sensor berbasis mikrokantilever. Kata Kunci : Mikrokantilever, sensor, sistem pegas, simulasi.